History of DNA sequencing technologyinig development - Urmanov Khurshid Nurzhanovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article discusses the stages of development of DNA sequencing technologies from the first (FGS) to the third generation (TGS).